2006
DOI: 10.2175/106143005x72993
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Effective Nocardioform Foam Control Measures for Non‐Selector Activated Sludge Systems

Abstract: Solids retention time (SRT), biological scum trapping and recycle, and the dynamic equilibrium between Nocardioform populations in the foam and the mixed liquor are the controlling factors in activated sludge foaming events caused by Nocardioform bacteria. For the operating modes described in this paper, a cured mixed liquor foaming condition (filament counts of approximately 10 5 intersections/g volatile suspended solids) was only achieved when SRT control, selective wasting, and polymer addition were in effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Combine Several Means of Control. Equivalent experience with another severe foam trapping process, the HPOAS process, indicates simultaneous application of several control measures at once could be successful, such as previously cited in this paper (Jolis, 2006). Also, the use of an anaerobic selector has been noted to reduce nocardioforms counts in the HPOAS process (Petit et al1997, Jolis et al 2005.…”
Section: Ifas Applicationsmentioning
confidence: 60%
See 1 more Smart Citation
“…Combine Several Means of Control. Equivalent experience with another severe foam trapping process, the HPOAS process, indicates simultaneous application of several control measures at once could be successful, such as previously cited in this paper (Jolis, 2006). Also, the use of an anaerobic selector has been noted to reduce nocardioforms counts in the HPOAS process (Petit et al1997, Jolis et al 2005.…”
Section: Ifas Applicationsmentioning
confidence: 60%
“…Anecdotally, it is reported that nuisance were avoided in the secondary clarifiers, but pumping nocardioforms to the digesters caused foaming there which required careful management of the problem (Parker et al, 2001 and. Selective Foam Wasting proved to be quite reliable in foam control when combined with SRT control and polymer addition measures in a later San Francisco HPOAS trial (Jolis et al, 2006).…”
Section: Hpoas Applicationsmentioning
confidence: 99%
“…Total control of biological foam in activated sludge systems is a rare event. A recent report ( Jolis et al, 2006 ) describes how it can be achieved through the combination of selective wasting and SRT control in the range 2 to 3 days. However, because biological nutrient removal plants typically operate at SRTs greater than 5 days, they cannot use SRT control.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming work showed that an anaerobic selector seemed quite effective for nocardioform control, when combined with SRT control and with sufficiently low SRT (Jolis et al, 2005). Due to the high level of foam trapping in the compartmentalized HPOAS system, a classifying selector was only partly successful at Sacramento in its first HPOAS application (Parker et al, 2003b), but proved to be quite reliable when combined with other measures in a later San Francisco trial (Jolis et al, 2006).…”
Section: The High Purity Oxygen Activated Sludge Processmentioning
confidence: 94%